Dry reforming of methane on bimetallic Pt–Ni@CeO2 catalyst: a in situ DRIFTS-MS mechanistic study. Issue 15 (1st July 2021) - Chen, Huanhao; Chansai, Sarayute; Xu, Shaojun; Xu, Shanshan; Mu, Yibing; Hardacre, Christopher; Fan, Xiaolei
Abstract : Bimetallic Pt–Ni catalysts can promote catalytic dry reforming of methane (DRM) with improved activity and deactivation resistance compared to the relevant monometallic catalysts. Abstract : Bimetallic Pt–Ni catalysts can promote catalytic dry reforming of methane (DRM) with improved activity and deactivation resistance compared to the relevant monometallic catalysts. Further development of Pt–Ni catalysts requires mechanistic insights into the catalytic system. Herein, a mechanistic study of DRM over Pt–Ni supported on cerium oxide catalysts ( i.e., Pt–Ni@CeO2 ) was performed using in situ coupled diffuse reflectance infrared Fourier-transform spectroscopy and mass spectrometry (DRIFTS-MS). Specifically, a comparative study of DRM over Pt–Ni@CeO2 and control materials under continuous temperature ramping, isothermal steady-state and fast cycling transient conditions was conducted to gain information on the key surface active intermediates. As compared with the Ni@CeO2 monometallic catalyst, the bimetallic Pt–Ni@CeO2 catalyst showed significantly enhanced performance regarding activity, H2 /CO ratio and long-term stability. In situ DRIFTS measurements revealed that CH4 decomposition on the surface of monometallic Ni phases readily caused serious coke deposition and deactivation. Conversely, the Pt phase in the bimetallic catalyst could improve CO2 dissociation, thus producing adsorbed oxygen species, which are beneficial for oxidising surface carbon species (derived from CH4 decomposition) to reduce coke formation. Meanwhile, the existence of Pt sites in the bimetallic catalyst could significantly improve metal dispersion, and thus facilitate the decomposition of CH4 .